2004
DOI: 10.1111/j.1365-2826.2004.01173.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Enrichment on Stress Related Systems in Rats

Abstract: The aim of this study was to test whether environmental enrichment alters the status and responsiveness of pituitary-adrenocortical and sympathetic-adrenomedullary hormones in rats. Previous studies have shown that rats kept in an enriched environment differ from those kept in standard cages in dendritic branching, synaptogenesis, memory function, emotionality and behaviour. In male Wistar rats kept in an enriched environment for 40 days, we studied basal concentrations of hormones, endocrine responses to 5-HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
124
2
15

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(154 citation statements)
references
References 50 publications
13
124
2
15
Order By: Relevance
“…Among factors that could account for the discrepant findings, the time of the light-dark cycle at which the samples were collected may be of major relevance (Cano et al 2008). Confirming previous reports in adult rats (e.g., Bakos et al 2009;Leal-Galicia et al 2007;Schrijver et al 2002; but see Moncek et al 2004), we observed that enrichment did not influence the basal corticosterone level, whatever the age.…”
Section: Basal Corticosterone Levelssupporting
confidence: 85%
“…Among factors that could account for the discrepant findings, the time of the light-dark cycle at which the samples were collected may be of major relevance (Cano et al 2008). Confirming previous reports in adult rats (e.g., Bakos et al 2009;Leal-Galicia et al 2007;Schrijver et al 2002; but see Moncek et al 2004), we observed that enrichment did not influence the basal corticosterone level, whatever the age.…”
Section: Basal Corticosterone Levelssupporting
confidence: 85%
“…They showed also a decrease in body weight gain, as observed at the end of experiment. These observations are in agreement with previous data obtained in rats (Moncek et al, 2004). Rats kept in an enriched environment also showed a reduction of body weight gain, increase in plasma corticosterone and adrenal gland enlargement.…”
Section: Acta Veterinaria Hungarica 56 2008supporting
confidence: 83%
“…These behavioural effects produced by environmental enrichment (EE) are, in part, mediated by changes in the activity of the HPA axis and the release of corticosterone [24]. Studies from our laboratory and others suggest that changes in the activity of the PFC, presumably infralimbic cortex, explain the reduced reactivity to stress that is observed in enriched animals [9,25,26].…”
Section: Introductionmentioning
confidence: 99%